ANALISIS LAGU CORNERSTONE KARYA HILLSONG WORSIP ARR. HEATHER SORENSON - Nova, Lidya Trivena; Hadijaya, Christanto; Malau, Martha Yuni (STT Kristus Alfa Omega, 2024)
The results of the research conducted by the researcher on the analysis of the Cornerstone Hillsong Worship song in the arrangement of Heather Sorenson. This analysis in general is by understanding Cornerstone's score on Heather Sorenson's arrangement, making it easier for researchers to analyze Cornerstone's song which includes musical form and harmony as well as interpretation of the meaning of the song from Heather Sorenson's arrangement. The Authentic Cadence motif is the most frequently used repetition motif, the period consists of 2 parts. The cadence in each phrase uses half cadence and perfect authentic cadence.